The role of low-temperature organic matter diagenesis in carbonate precipitation within a marine deposit. (January 2017) - Miyakawa, Kazuya; Ishii, Eiichi; Hirota, Akinari; Komatsu, Daisuke D.; Ikeya, Kosuke; Tsunogai, Urumu
Abstract: Carbonate minerals in veins can record paleo-hydrogeological information that enables the reconstruction of groundwater history. This paper investigates the cause of differences in the occurrence of carbonate veins in the Koetoi and Wakkanai formations, both Neogene mudstone units in northwestern Hokkaido, from the perspective of controls on CO2 supply from the alteration of organic matter. Carbonate veins are rare in the Koetoi Formation, but are widespread in the Wakkanai Formation. This area is a region of oil and gas accumulation where deep groundwater is saturated mainly with CH4 and CO2 . The results show high δ 13 C values in co-existing CH4 (∼–32.6‰) and CO2 (∼+31.0‰) gases. An investigation of δ 13 C – δD systematics among these gases indicates that isotopic fractionation was caused by microbial CO2 reduction. Although total organic carbon content in the Koetoi Formation decreases with increasing depth, total organic content in the Wakkanai Formation remains roughly constant with depth. Furthermore, although δ 13 C values also show depth dependence, values from the Wakkanai Formation are higher than those from the Koetoi Formation. This 13 C-enrichment could be explained by Rayleigh fractionation in a closed system. Based on these results, the processes behind the formation of the carbonate veins can be summarized as follows. Carbon dioxide behavior is thought to play an important role with respect to carbonate formation because CO2 abundance is closely linked to pH and pressure. In shallow sedimentary rocks such as the Koetoi Formation that have started to experience diagenetic alteration of organic matter, CO2 in groundwater is supplied by microbial decomposition of organic matter and is reduced to CH4 by methanogens. In deep sedimentary rocks such as the Wakkanai Formation that have undergone diagenesis but have only experienced moderate temperatures so that thermal decomposition of organic matter has not yet begun, microbial degradation of organic matter has proceeded too far for any more CO2 to be produced. Thus, carbonate precipitation is initiated when pH rises due to microbial CO2 reduction. The contrast between the occurrence of carbonate veins in the Koetoi and Wakkanai formations can be explained by our results, which can also be applied to general carbonate behavior in marine sedimentary rocks. Highlights: δ 13 C – δD systematics of coexisting CH4 and CO2 . Extreme- 13 C enrichment caused by microbial CO2 reduction in a closed system. Organic matter diagenesis plays an important role in carbonate precipitation.